INCOME AND SUBTITUTION EFFECT OF INDONESIAN LABOUR SUPPLY - Rindang Rayo Ranas (Universitas Islam Indonesia, 2011)
Indonesia is the fifth largest populated country in the world with abundance of labour supply. There are two types of analysis that can explain the phenomenon of labour supply, namely the income effect and substitution effect. The purpose of this study is to estimate the income effect and substitution effect of labour supply in Indonesia during 2005-2008. Using a panel data analysis technique, the results show that the income effect dominates the substitution effect in influencing the level of labour supply in Indonesia. This means that changes in labour income is more influential on a person's decision not to engage in the labour market.Keywords: Labour supply, income effect, substitution effect, panel dataJEL classification numbers: J01, J22, J29